ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NO. 46/PUU-VIII/2010 TENTANG PENGUJIAN UU NO. 1 TAHUN 1974 DALAM KONSEP LAQITH DAN WASIAT WAJIBAH Analysis of Constitutional Court Decision No. 46 / PUU-VIII / 2010 / on Judical Review Act No.1 of 1974 in The Concept Laqith and Wasiat Wajibah - Ikhsan Fatah Yasin (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2016)
Constitutional Court Decision No. 46 / PUU-VIII / 2010 raise the pro and contra in the society. The pro side considers the Constitutional Court decision gives justice for women who are victims of fraud or sirri wedding, and for the children born from this relationship. On the other hand, the contra side argues that the decision of the Constitutional Court has strayed far from the Islamic law; even they consider it as legalizing adultery. In this research, writer uses a qualitative approach. The writer deciphers Constitutional Court Decision No. 46 / PUU-VIII / 2010 and then analyzes those using concepts laqith and wasiat wajibah in the Islamic law. The concept of laqith can be used to justify the obligation of biological father toward his children, and wasiat wajibah can be used as a way out for inheritance for children born outside wedlock. From these results, it can be concluded that the court decision number 46 / PUU-VIII / 2010 does not contradict with the Islamic law.